Tender mercies [videorecording (DVD)] - Duvall, Robert; Harper, Tess; Hubbard, Al (Lions Gate Films, Inc., 2009)
An alcoholic drifter comes into the life of a lonely widow and her young son in the barren flatlands of Texas. But when Mac is revealed to be a once-famous country singer, he must confront a painful past that includes his bitter superstar ex-wife.